Geschichte Chinas 1279-1949 - Dabringhaus, Sabine 1962- (De Gruyter Oldenbourg, 2015)
Sabine Dabringhaus presents 700 years of Chinese history, from the Yuan Dynasty to Mao's rise to power. She addresses key topics in research, including the Chinese state, questions about periodization and interpretation, China's foreign relations and social structure, as well as modernization, reform, and revolution. An updated bibliography rounds out the revised third edition
Keywords: Geschichte 1270-1949; Geschichte 1279-1949; Geschichte Asiens; Geschichte; Area Studies -- Asia; History -- Historical Periods -- Contemporary History -- Contemporary History until 1945; History -- Historical Periods -- Modern History; History -- Regions and National Histories -- Asia-Pacific; Asien; China; Bibliografie